DINAMIKA MASYARAKAT BERAGAMA MENUJU NEGARA BALDATUN TOYYIBATUN WARABBUN GHAFUR (Sebuah Tinjaun Implementasi Teory Billyard Ball ) - Muhammad Nur; M. Samson Fajar (Universitas Muhammadiyah Metro, 2021)
Religion and society have a very close relationship in this life, fitroh humans will never be separated from belief in God, so that automatically applied in religious norms and values, while when humans are positioned as social beings who will not be able to stand alone then there is interaction between individuals, groups giving birth to society. Both religious and community items cannot be separated, because normatively that religion is derived to foster individuals and society. The methodology used in analyzing this study is literature study, which analyzes a variety of scattered texts related to the dynamics of a common society, which is progressing and leading to religious transformation towards civil society, or often called baldatun toyibatun warabbun ghafur. This study can be concluded that the dynamics of religious communities is an ongoing evolutionary process that is dynamically in accordance with the existing dynamics of thought, supported by other factors. The culmination of the dynamics of religious communities is when religion is able to become a coloring even as a formal symbol in a government, in which religious values ​​are the main reference in government. So that in the process religion began to participate practically in politics to gain power.